Association of metabolic syndrome and cognitive function in a population‐based cross‐sectional study of adults aged 60 years or older: Neuropsychology/Early detection of cognitive decline with neuropsychological tests. (7th December 2020) - Karanth, Shama D.; Katsumata, Yuriko; Nelson, Peter T.; Kryscio, Richard J.; Schmitt, Frederick A; Slade, Emily; Vsevolozhskaya, Olga; Fardo, David W.; Abner, Erin L.
Abstract: Background: Metabolic syndrome (MetS) is defined by the presence of five cardiovascular risk factors: diabetes, hypertension, high body weight, and hypercholesterolemia. Each factor has been reported to associate with cognition, but the association of MetS with cognitive function is not well understood. The current study explored the association of MetS with cognition in a nationally representative sample of elderly adults in the United States. Method: Cross‐sectional data from the National Health and Nutrition Examination Survey (NHANES 2011‐2014) were obtained for participants age ≥60 years. MetS was defined per American Heart Association criteria (≥ 3/5 factors). Cognitive performance was based on components of the Consortium to Establish a Registry in Alzheimer's disease (CERAD) neurocognitive battery. A composite z‐score was calculated for each CERAD component; z‐scores were then averaged to estimate global cognition (Figure 1). Memory complaint was based on self‐report. Linear regression models were fit to evaluate the association between global cognition and MetS, and logistic regression was used to evaluate the association of memory complaint with MetS; we used survey statistics to account for the complex NHANES sampling design. Result: Included participants (n=2593) were mean 69.4 years old; 54.8% (n=1318) were female. MetS was present in 60.9% (n=1633) of participants. After adjustment for age, sex, race/ethnicity, education, alcohol use, poverty, marital status, and memory complain, MetS was associated with almost 1/3 standard deviation lower mean global cognition compared to participants with no MetS factors (β= ‐0.28; 95%CI ‐0.46, ‐0.10), while participants with 1‐2 MetS conditions had similarly lower cognitive scores relative to participants with none (β= ‐0.23; 95%CI ‐0.42, ‐0.04) (Table 1). After adjustment for age, sex, race/ethnicity, education, alcohol use, poverty, marital status, and z‐score, MetS was not significantly associated with memory complaint (OR=0.90; 95%CI 0.33, 2.45). Conclusion: Our findings suggest that MetS was associated with lower cognitive performance in older adults, but this association may be modified by participant characteristics. Participants who did not meet criteria for MetS but had 1‐2 risk factors showed similar cognitive performance to those with MetS, so focusing on dichotomous MetS classifications may obscure cognitive risks for those individuals who don't fully meet the MetS criteria.